A novel telemedicine technique for evaluation of ocular exam findings via smartphone images. (April 2022) - Sink, Joshua; Blatt, Stephen; Yoo, David; Henry, Michael; Yang, S Daniel; Vasaiwala, Roshni; Ghadiali, Larissa; Adams, William; Bouchard, Charles S
In this study, we compared the assessment of remote smartphone photographs to in-office exams in the diagnosis of two groups of external eye diseases, red-eye pathology and post-operative eyelid surgery complications. Participants were examined and received an in-office diagnosis by either a corneal or oculoplastic specialist. After viewing an educational video on smartphone photography, the patient's companion then took a series of standardized photographs. Two additional corresponding specialists then made a separate diagnosis via the interpretation of only smartphone images and the patient's history. 'Remote' and in-office diagnoses were compared using a kappa test for agreement. The remote and in-office diagnoses were in agreement for 27 of 28 eyes, representing a chance-corrected Kappa agreement rate of 93% (95% confidence interval: 79–99%). Among the 16 red eyes, the diagnoses were in agreement for 15 of 16 red eyes, representing a chance-corrected Kappa agreement rate of 92% (95% confidence interval: 77–99%). Among the 12 eyes with post-operative eyelid surgery complications, the diagnoses were in perfect agreement. Our results suggest that the diagnosis of 1) red-eye pathology and 2) post-operative eyelid surgery complications based on smartphone images may be comparable to in-office exams.